Prevalence and factors associated with undernutrition and anaemia among school children in Durbete Town, northwest Ethiopia - Alelign, Tilahun (Arch Public Health, 2015)
BACKGROUND: Information about risk factors of undernutrition and anaemia is useful to design appropriate strategies to control the health problems. In this study, the prevalence and factors associated with undernutrition and anaemia were assessed among school children in Abchikeli and Ayalew Mekonnen Elementary Schools, northwest Ethiopia, in February and March 2010. METHODS: A cross-sectional study was carried out among 384 school children. Stool samples were examined using single Kato-Katz slide and nutritional status was determined using anthropometry technique. A pre-tested standardized questionnaire was used to gather information on the socio-demographic and the socio-economic status of the school children. Multivariate logistic regression analysis was used to quantify the association of intestinal helminth infection and socio-demographic and socio-economic factors with undernutrition and anaemia. RESULTS: Out of 384 children examined, 32.3 % were undernourished (27.1 % underweight and 11.2 % stunted) and 10.7 % were anaemic. The odds of stunting were approximately seven times higher in children of ages 10 to 14 [Adjusted Odds Ratio (AOR) = 6.93, 95 % CI = 2.60, 18.46] and 2.5 times higher in males [AOR = 2.50, 95 % CI = 1.24, 5.07] than children of ages 5 to 9 and females, respectively. The odds of underweight was three times higher in children who did not wash their hands before eating compared to those who did wash their hands [AOR = 3.13, 95 % CI = 1.19, 8.17]. The chance of anaemia was nine times higher in children who were infected with hookworms compared to those who were not infected with any helminth species [AOR = 8.87, 95 % CI = 2.28, 34.58]. The odds of being undernourished and anemic were similar among children with different socio-economic status. CONCLUSIONS: Undernutrition and anaemia are public health problems of school-age children in Durbete Town. Health education and provision of additional food supplements would be important to reduce the problem of undernutrition among school-age children in the town. Deworming of children in the town would also have additional impact on reducing the level of anaemia.